Private Equity Exits in the CEE: An Exploratory Analysis of Exit Routes and Holding Periods - Bílek, Michael (Vysoké učení technické v Brně, Fakulta podnikatelská, 2024)
Purpose of the article: The purpose of this article is to assess private equity exit strategies of CEE portfolio companies with regards to desired exit routes, including a cross-border deal aspect and a pre-exit holding period. Methodology/methods: This paper employs secondary data from the Mergermarket database containing information on more than 20 thousand private equity M&A deals and IPOs. General scientific methods such as analysis, comparison or generalization were used. Scientific aim: Only limited amount of research was carried out on the private equity exits in the region of central and eastern Europe. This study aims at shedding new light on understanding of private equity exit route decisions and timing in this particular geographic area. Findings: Exiting a CEE portfolio company, private equity investors tend to prefer exiting via trade sales over secondary buyouts or IPOs. They also tend to prefer foreign acquirers over domestic ones. A typical pre-exit holding period averages around 5 years. Conclusions: Our results show that while exiting a CEE portfolio company, private equity investors tend to divest by selling the company to a strategic investor (trade sales) rather than a financial investor (secondary buyouts) or exiting via an IPO. While exiting via trade sales and secondary buyouts, private equity investors tend to prefer foreign acquirers rather than domestic ones with a strong preference of acquirers from outside of the respective region. Typical holding period of a CEE private equity portfolio company remains on average in line with academic theory. Our paper contributes to the developing literature of private equity by using an extended and up to date dataset and introducing the research on the cross-border aspect of PE exit strategies.
Keywords: IPO; trade sales; secondary buy out; divestment; private equity